Ontogeny-Specific Skeletal Deformities in Atlantic Haddock Caused by Larval Oil Exposure - Olsvik, Pål A.; Sørhus, Elin; Meier, Sonnich; Torvanger, Ingrid; Thorbjørnsen, Maja; Thorsen, Anders; Sørensen, Lisbet; Fjelldal, Per Gunnar; Karlsen, Ørjan; Guimaraes, Igo G.; Lie, Kai K. (Frontiers in Marine Science, 2021)
Bone deformities are one of the main effects of crude oil exposure in marine fish larvae. Craniofacial and jaw deformities, if severe enough, may restrict feeding and ultimately kill the developing larvae. This study aimed to examine the impact of dispersed crude oil on bone development in Atlantic haddock (Melanogrammus aeglefinus) larvae, a fish species spawning in areas approached for oil and gas exploration in the North Atlantic Ocean. Atlantic haddock larvae were exposed to low (60 µg oil/L), high (600 µg oil/L) or pulsed (0-600, average 60 µg oil/L over time) dispersed crude oil from 0-18 days post hatch (dph). Endpoints included survival and growth, bone integrity, and transcriptional parameters, assessed during exposure (0-18 dph) and after exposure until the fish reached 8-month of age (243 dph). The results showed that larvae in the high treatment group had reduced growth at 2-19, 44, 134 and 243 dph. Craniofacial abnormalities were the most severe at 8 and 19 dph. These deformities were not present at 44 dph, possibly because larvae with deformed jaws failed to feed properly and died. Higher prevalence of spinal deformities was observed in haddock that survived to 243 dph. Three genes encoding proteins critical for osteoblast function, sp7, postn and col10a1, were downregulated in the high treatment group larvae. We discuss possible mechanisms of action in the developing larvae after oil exposure. In conclusion, this study shows that larval exposure to oil potentially can have long-term effects on growth and bone integrity in Atlantic haddock.